2014
DOI: 10.1371/journal.pone.0092246
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Induction Improves Cardiac Function following Myocardial Ischemia by Reducing Oxidative Stress

Abstract: BackgroundOxidative stress plays a key role in exacerbating diabetes and cardiovascular disease. Heme oxygenase-1 (HO-1), a stress response protein, is cytoprotective, but its role in post myocardial infarction (MI) and diabetes is not fully characterized. We aimed to investigate the protection and the mechanisms of HO-1 induction in cardiomyocytes subjected to hypoxia and in diabetic mice subjected to LAD ligation.MethodsIn vitro: cultured cardiomyocytes were treated with cobalt-protoporphyrin (CoPP) and tin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 47 publications
3
50
0
Order By: Relevance
“…Significant increase in the proinflammatory transcripts viz ccl2, Il-1␤, ccl8, and ccr2 (neutrophil chemotaxis and leukocyte migration genes), with no change in the proresolving/alternative transcript Il-10 and Il-13, in CBK mice indicates an impaired defensive mechanism to repair inflammation at 28 wk of age. This was further supported by decreased levels of 5-LOX, COX-2, and HO-1 (3,17,19), impairing the resolution of the inflammation axis. Thus an age-related defective resolution of inflammation and dilative ventricular dysfunction leads to reduced survival (42) with marked cardiomyopathy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Significant increase in the proinflammatory transcripts viz ccl2, Il-1␤, ccl8, and ccr2 (neutrophil chemotaxis and leukocyte migration genes), with no change in the proresolving/alternative transcript Il-10 and Il-13, in CBK mice indicates an impaired defensive mechanism to repair inflammation at 28 wk of age. This was further supported by decreased levels of 5-LOX, COX-2, and HO-1 (3,17,19), impairing the resolution of the inflammation axis. Thus an age-related defective resolution of inflammation and dilative ventricular dysfunction leads to reduced survival (42) with marked cardiomyopathy.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, to understand how Bmal1 deletion affects the inflammation-resolution axis at 28 wk, we determined mRNA levels of resolving genes. The CBK mice showed a significant decrease in proresolving transcripts of Hmox-1, Alox5, and Ptgs-2 (3,17,19) with no change in levels of inflammation promoting transcripts Alox12 and Alox15 (21) compared with age-matched controls (Fig. 6, A and B).…”
Section: Cbk Mice Develop Age-related Cardiac Hypertrophymentioning
confidence: 92%
“…First, we observed a 2-3 fold increase in HO-1 enzymatic activity at 18 hrs post FeS/SnPP treatment, confirming active HO-1 generation (i.e., vs. production of a ‘dead’ enzyme). Second, we utilized a functional way (29) of determining HO-1's enzymatic participation in the observed cytoresistance. To this end, we preconditioned mice with FeS/SnPP, driving up renal HO-1 protein levels, and then 18 hrs later, we administered SnPP to inhibit the pre-formed HO-1 activity at the time of injury induction.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that when cultured cardiomyocytes were treated with cobalt protoporphyrin (CoPP), prior to hypoxic stress, HO-1 levels were increased and the hypoxic damage was reduced. Tin protoporphyrin (SnPP) abolished the beneficial effects of CoPP pretreatment (Issan et al 2014). It is unlikely that TNF␣ protected the cardiac cells from hypoxia by inducing HO-1, as it has been demonstrated that HO-1 induction reduces the levels of inflammatory cytokines such as TNF␣, IL-6, and IL-1␤; a process that is reversed by inhibiting HO activity (Hosick and Stec 2012).…”
Section: Discussionmentioning
confidence: 99%